Is device-based total and domain-specific sedentary behaviour associated with psychological distress in Flemish workers?. (3rd September 2020) - De Cocker, Katrien; Ketels, Margo; Bennie, Jason A; Clays, Els
Abstract: Background: There is increasing interest in the association between psychological distress and time spent in sedentary behaviour (e.g. sitting), a highly prevalent behaviour in modern society. The limited evidence is mixed and mainly based on studies using self-reported sedentary time. Few studies have investigated device-based total sedentary time in its association with distress. None, however, have examined device-based domain-specific sedentary time in relation to psychological distress. The aim of this study was to investigate whether device-based total and domain-specific sedentary behaviour were associated with psychological distress. Methods: Flemish employees ( n = 401; 20–64 years; 42.6% male; 83.6% had a 'physically active occupation') of seven organizations in service and production sectors participated. Sedentary behaviour (exposure) was assessed by two Axivity AX3 accelerometers (one placed on the thigh and one placed between the shoulders) for two to four consecutive working days. Based on diary completion, domain-specific sedentary behaviour (leisure vs. work) was assessed. The 12-item General Health Questionnaire was used to assess psychological distress (outcome). Adjusted hierarchical multiple regression models were conducted to report on the associations between total and domain-specific sedentary behaviour and psychological distress. Results: About 35% of the sample had high levels of distress and average total sedentary time was 7.2 h/day. Device-based total sedentary behaviour [ B = −0.009, 95% confidence interval (CI), −0.087 to 0.068], leisure-time ( B = 0.001, 95% CI, −0.017 to 0.018) and work-related ( B = 0.004, 95% CI, −0.006 to 0.015) sedentary behaviour were not significantly associated with psychological distress. Conclusion: This cross-sectional study examining the association between device-based total and domain-specific sedentary behaviour and psychological distress among employees showed a lack of significant findings.